2017
DOI: 10.1080/00207454.2017.1358716
|View full text |Cite
|
Sign up to set email alerts
|

Hypophonia as a sign of thalamus lesion: a case report

Abstract: Hypophonia is a neurological sign usually seen after brainstem or peripheral damage, either at the recurrent laryngeal nerve or vocal cord level. However, it has been described as a sign of supratentorial strokes in a few studies, specifically when anterior and ventral thalamic involvement is reported. In addition, it is a prominent sign of other neurological disorders such as Parkinson disease and other extrapyramidal conditions. We describe a case of hypophonia secondary to a left thalamic hemorrhage, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Perhaps, disruptions of the thalamo-striato-cortical loop at the anterior and ventral thalamus level could explain the observed speech deficits. It is worth noting that hypophonia has been mainly reported after dominant thalamus lesions[ 7 , 10 ] while our patient suffered right thalamic hemorrhage. In a study of right-handed Parkinson’s patients, Liotti et al [ 11 ] observed activation of the right anterior insula, caudate head, putamen, and dorsolateral prefrontal cortex after successful treatment of hypophonia.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Perhaps, disruptions of the thalamo-striato-cortical loop at the anterior and ventral thalamus level could explain the observed speech deficits. It is worth noting that hypophonia has been mainly reported after dominant thalamus lesions[ 7 , 10 ] while our patient suffered right thalamic hemorrhage. In a study of right-handed Parkinson’s patients, Liotti et al [ 11 ] observed activation of the right anterior insula, caudate head, putamen, and dorsolateral prefrontal cortex after successful treatment of hypophonia.…”
Section: Discussionmentioning
confidence: 62%
“…They suggested that the anterolateral thalamic lesion that disrupted extrapyramidal pathways might be a major factor in producing dysphonia and that the predominantly anterior and possibly lateral thalamic lesions were responsible for hypophonia. Recently, Rodríguez-López et al [ 7 ] presented a case report of hypophonia secondary to a left thalamic hemorrhage. They speculated that a thalamo-striato-cortical loop might play an important role in controlling voice modulation, and disruptions of this loop precisely at the anterior and ventral thalamus level would result in hypophonia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations